The interplay between inflammation, immunity and commensal microflora in glaucomatous neurodegeneration - Henein, Christin; Khaw, Peng T. (Annals of Eye Science, 2019)
The immensely diverse and rich human gut microbiome has a huge potential to impact health and disease (1). Gut microbiome dysbiosis has been associated with gastro-intestinal inflammatory conditions and extra-intestinal disorders; such as stroke, depression, neurodegenerative, cardiovascular and metabolic disorders (2-6). In the September 2018 issue of nature communications, Chen and colleagues report the findings from a study that found commensal microflora-induced T cell responses mediate progressive neurodegeneration in glaucoma, in mouse glaucoma models (7).